Crazy Mountain Kiss : Sean Stranahan #4 - McCafferty, Keith; Holmes, Rick, 1963-; Recorded Books, LLC. (Prince Frederick, MD : Recorded Books, 2015)
"It's April, but there's still snow on the Montana mountains the day a member of the Madison River Liar and Fly Tiers club finds a Santa hat in the chimney of his rented cabin. With the flue clogged and desperate to make a fire, he climbs up to the roof, only to find the body of a teenage girl wedged into the chimney. When Sheriff Martha Ettinger and her team arrive to extract the body they identify the victim as Cinderella "Cindy" Huntingdon, a promising young rodeo star, missing since November. Was Cindy murdered? Or running for her life--and if so, from whom? Cindy's mother, Etta, hires private detective Sean Stranahan to find out. Jasper Fey, the girl's stepfather, believes moving on is the only way to heal. But Etta's not willing to let it go, and neither are Sean or Martha, who find clues to the death in the mysterious legends of the Crazy Mountains.
Title from container.
Compact disc.
In container (17 cm.).
Narrated by Rick Holmes.
Keywords: Private investigators -- Fiction; Murder -- Investigation -- Fiction; Missing persons -- Fiction; Mystery fiction; Audiobooks